Multilevel modeling for dental caries among adolescents in a Brazilian large city - Giovana Daniela Pecharki; João Armando Brancher; Márcia Olandoski; Andrea Duarte Doetzer; Samuel Jorge Moyses; Paula Cristina Trevilatto (University Library System, University of Pittsburgh, 2016)
Dental caries is a complex disease, which needs an approach that considers caries influencing factors at different levels and their integration. Multilevel Modeling is a clustered analysis of variables from the individual to the community level. The aim of this study was to investigate the association of social and biological factors grouped into hierarchical levels, in students with caries. A sample of 687 students was evaluated from public and private schools of Curitiba. The parameters evaluated were: individual level, school level and district level. Individual variables had a highly significant association with caries experience, also in the presence of school and district levels. Male sex negatively associated with caries experience. However, the interaction between male sex and no fluoride use was positively associated with caries. Lower socioeconomic status, dental biofilm, and fluorosis were associated with caries. Nevertheless, the interaction between dental biofilm and fluorosis was negatively associated with caries experience. The interaction between no flossing and use of public dental services were also associated with caries outcome. Individual factors were associated with caries experience even with the inclusion of contextual variables in the study population.